Traditional Chinese and Thai medicine in a comparative perspective - He, Ke (Complement Ther Med, 2015)
The work presented in this paper compares traditional Chinese medicine and traditional Thai medicine, expounding on origins, academic thinking, theoretical system, diagnostic method and modern development. Based on a secondary analysis of available literature, the paper concentrates on two crucial historical developments: (1) the response to, and consequences of, the impact of the Western medicine; and (2) the revival of traditional medicine in these two countries and its prospects. From a comparative perspective, the analysis has led to the conclusion that the rise and fall of traditional medicine is an issue closely related with social and political issues; and the development of traditional medicines requires national policy and financial support from governments, human resource development, the improvement of service quality, and the dissemination of traditional medicine knowledge to the public. In addition, this paper also suggests deepening exchanges and cooperation between China and Thailand, strengthening cooperation between traditional medicine and medical tourism.